2011
DOI: 10.1063/1.3592652
|View full text |Cite
|
Sign up to set email alerts
|

Neoclassical physics in full distribution function gyrokinetics

Abstract: Treatment of binary Coulomb collisions when the full gyrokinetic distribution function is evolved is discussed here. A spectrum of different collision operators is presented, differing through both the physics that can be addressed and the numerics they are based on. Eulerian-like (semiLagrangian) and particle in cell (PIC) (Monte-Carlo) schemes are successfully cross-compared, and a detailed confrontation to neoclassical theory is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 85 publications
2
42
0
Order By: Relevance
“…The right-hand side of (1) contains the collision operator C(F ), which is implemented im Gysela as a Fokker-Planck type operator acting on v G only. This operator conserves density, momentum and energy, and it was demonstrated that it allows one to recover the main results of neoclassical theory, in particular concerning the predictions for heat transport and poloidal rotation, including their dependence on aspect ratio and collisionality [23]. Additionally, the source term S provides a constant input of heat in the system.…”
Section: Flux-driven Simulations With the Gyrokinetic Code Gyselamentioning
confidence: 99%
“…The right-hand side of (1) contains the collision operator C(F ), which is implemented im Gysela as a Fokker-Planck type operator acting on v G only. This operator conserves density, momentum and energy, and it was demonstrated that it allows one to recover the main results of neoclassical theory, in particular concerning the predictions for heat transport and poloidal rotation, including their dependence on aspect ratio and collisionality [23]. Additionally, the source term S provides a constant input of heat in the system.…”
Section: Flux-driven Simulations With the Gyrokinetic Code Gyselamentioning
confidence: 99%
“…In both codes, only the ion distribution functions are calculated and electrons are assumed to respond adiabatically to the electric potential on a flux surface. Coulomb collisions are not included in the XGC1p simulations, while a Fokker-Planck operator acting on v is included in Gysela [20]. The collisionality ν * = 0.1 and the total simulation time is roughly 0.3 collision time for Gyselasimulation.…”
Section: Simulation Approach and Momentum Conservationmentioning
confidence: 99%
“…Here K 1 is formed by evaluating the impurity concentration and parallel viscous matrix elements. Calculations of the coefficient K 1 can be done analytically [19], numerically [35,36], or determined from plasma simulations [37,38,39].…”
Section: Neoclassical Theorymentioning
confidence: 99%